Turkeys - Endres, Hollie J. (Minneapolis : Bellwether Media, 2008)
Simple text and full color photographs provide a basic introduction to turkeys and how they live on a farm.
Includes bibliographical references (p. 23) and index.
1.5
K-3
Keywords: Turkeys -- Juvenile literature; Turkeys; Turkeys; Turkeys